History of money, banking and finance.
1 online resource.
Keywords: This 14-volume set collects together a series of key titles that provide a wide-ranging analysis of money (A Survey of Primitive Money), banking (Bank Behavior, Regulation and Economic Development) and finance (The Money Market). Other titles expand on these topics, giving both a wider overview and a more detailed snapshot of the subjects covered.